2004
DOI: 10.1124/dmd.32.5.484
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cyp2c9 Genetics and Oral Contraceptives on Cytochrome P450 2c9 Phenotype

Abstract: ABSTRACT:CYP2C9-dependent drug metabolism is subject to large interindividual variation. To some extent, this is explained by genetic polymorphism with expression of enzyme variants that differ in catalytic activity. The aim of this study was to characterize the variation in CYP2C9 phenotype in relation to genotype, with further analysis of the CYP2C9 gene in metabolic outliers. A study population of 126 healthy white subjects were recruited and genotyped for the variant alleles, CYP2C9*1-3. In CYP2C9 phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 27 publications
2
37
0
1
Order By: Relevance
“…This is in agreement with previous reported allele frequencies in other Caucasians [30]. 95% (95% CI 84.2-99.4%) of the subjects with CYP2C8*3 alleles also carried CYP2C9*2 alleles, while 75% (95% CI 61.0-85.3%) of the subjects having the CYP2C9*2 variant also carried CYP2C8*3 alleles.…”
Section: Resultssupporting
confidence: 82%
“…This is in agreement with previous reported allele frequencies in other Caucasians [30]. 95% (95% CI 84.2-99.4%) of the subjects with CYP2C8*3 alleles also carried CYP2C9*2 alleles, while 75% (95% CI 61.0-85.3%) of the subjects having the CYP2C9*2 variant also carried CYP2C8*3 alleles.…”
Section: Resultssupporting
confidence: 82%
“…Furthermore previously it is reported that OC use inhibits CYP2C19 enzyme activity [18] and F o r P e e r R e v i e w 4 hence variation in OC use habit may also contribute to some extent. As to our knowledge no study has compared the enzyme activity between the two populations controlling for the effect of confounding factors such as oral contraceptive use and CYP2C19 genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Christensen et al [18] developed the Karolinska cocktail based on five probe drugs to phenotype the enzymes CYP1A2, CYP2C9, CYP2D6, CYP3A4 and CYP2C19. In general previous studies reported lower CYP2C19 enzyme activity among Asians compared to White population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2C8*3 is defective in the metabolism of two important CYP2C8 substrates: the anticancer drug paclitaxel (Bahadur et al, 2002) and the physiologically important compound arachidonic acid (AA) (Dai et al, 2001). In addition, variants CYP2C8*4 and CYP2C9*2 and CYP2C9*3 also have a lower metabolic activity than the wildtype variants (Bahadur et al, 2002;Griskevicius et al, 2003;King et al, 2004;Sandberg et al, 2004).…”
mentioning
confidence: 99%